A new case of West-East differentiation of the freshwater fauna in Northern Eurasia: the Pleuroxus trigonellus species group (Crustacea: Cladocera: Chydoridae) - Garibian, Petr G.; Neretina, Anna N.; Klimovsky, Alexey I.; Kotov, Alexey A. (Zootaxa, 2018)
Cladocerans (Crustacea: Branchiopoda) of Northern Eurasia traditionally belong to the most intensively studied groups of freshwater microcrustaceans. However, despite a significant progress in our knowledge of different aspects on their biology, some intriguing questions remain unresolved. The hypothesis of cladoceran faunas differentiation between the western and eastern parts of Northern Eurasia agrees with the continental endemism concept. But to date few cladoceran species groups have been investigated through the whole North Eurasian range. Our current work contributes to the confirmation of this hypothesis through a revision of the poorly studied Pleuroxus trigonellus species group. Based on material from Europe, we redescibed morphology of Pleuroxus trigonellus (O.F. Müller, 1776) s.str. and found that its distribution range is potentially restricted to the western portion of Northern Eurasia. At the same time, morphologically similar populations from the eastern portion of Eurasia belong to a new species, Pleuroxus yakutensis sp. nov. These two species are basically similar in general morphology of parthenogenetic and gamogenetic females, but have clear differences in the male morphology. Additionally we offer an identification key for discrimination of the P. trigonellus group from P. uncinatus (Baird, 1850) according to morphological features of the males.